æµ…æžSANTO PAULUS é«˜ä¸äºŒå¹´çº§ç†ç§‘å¦ç”Ÿçš„æ±‰è¯å¦ä¹ å›°éš¾ - Crista, Cindy; Thamrin, Lily; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIn Pontianak some schools have opened Chinese classes, and some schools have turned Chinese classes into compulsory courses. However, students listening, speaking, reading and writing abilities in Chinese classroom learning are insufficient. Students encounter some difficulties in learning Chinese, so they find it difficult to learn Chinese. The author investigates the second grade science students in Santo Paulus High School, and analyses the factors of students difficulty in learning Chinese. This paper uses the questionnaire method to analyze the students learning situation. Summarize some learning difficulties that Santo Paulus High School sophomores also encounter, such as: Chinese teachers do not adequately carry out the principle of